Activated sludge separation problems : theory, control measures, practical experience - Tandoi, Valter, ....-; Jenkins, David Trevor, 1943-; Wanner, Jiří, 1953- (London : IWA, 2006)
The Activated Sludge (AS) Process is old technology but is still widely adopted worldwide for its convenience and simplicity: an impressive number (many hundred of thousands) of this kind of system are in operation. Occasionally, problems such as bulking and foaming occur, causing regulation violations and large investment is often required immediately to control them. For this reason, an intense research effort has been made during the last few decades to face these problems, and this report details the work undertaken by the IWA Specialist Group on Activated Sludge Population Dynamic <http://www.iwahq.org.uk/template.cfm?name=sg17 > . This Scientific and Technical Report describes the main reasons for the growth of the different filamentous microorganisms in activated sludge, and the biological molecular tools available today for the identification of the main biomass components. The wide range of experiences around the world is documented and the methods to avoid the proliferation of these organisms are presented and critically reviewed.
Keywords: Actief slib; Afvalwaterzuivering; Microbiologie